The Effect of Promotion Strategy and Product Innovation on Myrepublic Product Promotion Performance - Galih Supraja (Proceeding of The International Conference on Economics and Business, 2022)
The use of technology is currently growing rapidly. A new invention known as fixed broadband was introduced along with the increasing telecommunication and information technology consumers by PT. Eka Mas Republik through the launch of a new product called MyRepublic. The purpose of this study was to examine the influence of product innovation and market-focused promotional tactics on the effectiveness of MyRepublic product promotions in Jakarta. Survey studies using a quantitative methodology is the method used. MyRepublic users and members, especially families who live in the Jakarta area, are the population of this study. A sample of 68 respondents was collected and evaluated for the effectiveness of this study. Multiple linear regression analysis is the technique used in this study for data analysis. The study findings show that the marketing plan significantly influences the success of the promotion. This implies that the success of the company's promotion will be better if the promotion plan of the staff is getting better. The effectiveness of promotion is greatly influenced by the progress of the product. This implies that marketing success will be better if product discovery is done better. Because today's information technology is developing so quickly, businesses must continuously incorporate innovation into their products.